The school library of Dayspring Academy a developmental plan - Meneses, Erwina T.; Sison, Josephine C.; Gonzales, Grace Marie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
A library is an integral part of a school. It is often referred to as the center of information in a school. It works hand-in-hand with schools to provide quality education and to producing information literate individuals and lifelong learners. This study aimed to develop a library for Dayspring Academy, a library wherein the school librarian works together with the faculty in teaching and imparting knowledge to the students.
The descriptive survey method was used in this study. A survey was conducted of the students to come up with a community analysis to be able to know the users' needs. Interviews were conducted with the administrator and faculty to understand their needs and to know their perceptions of the library and how this can be of importance to them. An ocular inspection was also made to be able to know the collection first hand and to inspect the location provided for the library. Record analysis was also conducted to further understand the school situation.
The study recommends the following for the development of the school library: 1) develop a collection development plan; 2) have a basic collection based on the proposed school library standards; 3) develop a manual of operations; 4) evaluate the existing library space to come up with suitable floor plan; 5) study the startup cost and come up with a 5 year breakdown of the anticipated expenses; 6) hire a trained librarian; 7) the directress, being a propeller for change, must conduct regular meetings with her faculty and staff; 8) have a user education program; and 9) have a promotion program.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- Philippines -- Quezon City; Library planning -- Philippines -- Quezon City